Efficacy of GMI, a fungal immunomodulatory protein, for head and neck cancer patients with chemotherapy-related oral mucositis: An open-labeled prospective single-arm study. Issue 16 (22nd April 2022) - Lu, Hsueh-Ju; Li, Che-Hsing; Kang, Yu-Ting; Wu, Chi-Mei; Wu, Chih-Hsien; Ko, Jiunn-Liang; Wu, Ming-Fang
Abstract: Background: Cancer patients usually suffer from intensive chemotherapy-related oral mucositis (OM), yet limited effective treatment can rapidly alleviate OM severity. Methods: This prospective study examined the efficacy of Reishimmune-S containing one fungal immunomodulatory protein, GMI on OM in patients with head and neck cancer. Patients with head and neck cancer and the diagnosis of chemotherapy-related OM were enrolled randomizedly to receive standard supportive care with/without Reishimmune-S 500 mg/day orally for consecutive 14 days. Due to intolerance to standard supportive care alone in the control arm, only the experimental arm with Reishimmune-S supplementation was analyzed in our trial. OM grading was evaluated as the primary outcome on day 1, 8, and 15. Secondary outcomes were absolute neutrophil counts and quality of life assessed by the EORTC-QLQ-H&N 35 questionnaire on day 1, 8, and 15. Results: Reishimmune-S supplement significantly reduced OM grading both at day 8 and 15. Trouble with social contact and weight loss conditions were also improved by Reishimmune-S. Reishimmune-S did not significantly affect absolute neutrophil counts during the 15-day follow-up. Conclusion: Reishimmune-S supplement potentially alleviates the severity of chemotherapy-mediated OM.